Genetic Transformation in White Jute Through Agrobacterium and Salinity Screening of Transgenic Plant (Bangladesh Journal of Agricultural Research, 2012)
The experiment was conducted to establish an efficient and reproducible protocol for the plant regeneration and genetic transformation in white Jute (Corchorus capsularis L.). The regeneration and transformation processes depend on optimum growth conditions, suitable explants and varieties. An  attempt was made for Agrobacterium mediated genetic transformation in white jute varieties using gene construct conferring both salt and drought tolerance (CIPK and Gly-1) along with the marker genes. Interestingly the two varieties (CVL-1 and Tricap-1) showed the response of both callus induction and plant regeneration on a single formulation i.e. MS medium supplemented with 2.0 mg/l BAP and 0.5 mg/l IAA. Explants were dipped to liquid culture of bacteria for one minute and then transferred to co-cultivation media for 24 hours. Shoot regeneration from Agrobacterium infected cotyledon was found highest in variety CVL-1 (43%) than Tri cap (38%). After co-cultivation and selection histochemical GUS assay was performed in different varieties (vars. Tricap-1, CVE-3 & CVL-1). In the transformed explants, GUS reporter gene was expressed showing blue colour in the explants tissues. Among the varieties CVE-3 showed the highest expression blue colour in the explants tissues. Those transgenic plants are transferred to salt medium and soil for evaluation. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11180 Bangladesh J. Agril. Res. 37(1): 97-107, March 2012